THE EFFECT OF STOCK SPLIT ANNOUNCEMENT ON THE TRADING VOLUME ACTIVITY, ABNORMAL RETURN, AND BID ASK SPREAD (STUDY ON COMPANIES LISTED ON THE IDX FOR THE PERIOD OF 2015 - 2019) - Diamanta Putri, Rimada Diamanta Putri; Pardomuan Sihombing (Dinasti Publisher, 2020)
This research is motivated by companies that carry out corporate actions in the form of stock splits. The corporate action aims to increase the liquidity of the outstanding shares and to give a positive signal to the company's performance in the future. To find out whether this signal is true or not, it is necessary to test market efficiency which proves that the stock split has an effect on changes in stock trading volume, abnormal returns and the bid ask spread. This type of research is the event study research with a quantitative approach. A sample of 66 companies using purposive sampling technique. The company under study is a company that carried out a stock split and is listed on the Indonesia Stock Exchange for the period 2015 - 2019. The type of data used in this study is secondary data in the form of daily data on sales of shares, number of shares outstanding, stock price (close price), price index. joint stock, stock offer and bid during the period 2015 - 2019. The results of the research through the Wilcoxon Signed Ranks Test with the results (1) There is no significant difference between stock trading volume before and after the stock split; (2) There is a significant difference between abnormal returns before and after the stock split; (3) There is no significant difference between the bid ask spread before and after the stock split.